Cobalt(II) Coordination Polymer Based on Dicarboxylate and Nitrogen-Containing Ligands - Wang, Yujing (Asian Journal of Chemistry, 2014)
A new coordination polymers [Co(5-NO2-ip)(bimb)]n (1) [5-NO2-ip = 5-nitro isophthalic acid, bimb = 1,4-bis(1-imidazol-yl)-2,5-dimethyl benzene], has been prepared by hydrothermal synthesis. Complex [Co(5-NO2-ip)( bimb)]n (1), is monoclinic, space group P21/c with a = 10.228 (5) Å, b = 16.804 (5) Å, c = 12.488 (5) Å, b = 91.771 (5)° V = 2145.3 (15) Å3, Z = 4, Mr = 506.34, Dc = 1.568 g/cm3, F (000) = 1036 and μ = 0.85 mm-1. The final refinement gave R = 0.0321 and wR = 0.0809 for 4072 reflections with I > 2s(I). X-ray diffraction analysis reveals that complex 1 shows a two-dimensional (2D) layer structure and features a three-dimensional supramolecular structure.